The archaeology of sanitation in Roman Italy : toilets, sewers, and water systems - Koloski-Ostrow, Ann Olga (The University of North Carolina Press, 2016)
Through the archeological record, graffiti, sanitation-related paintings, and literature, Ann Olga Koloski-Ostrow offers unique insights into Roman sanitation, engineering, urban planning and development, hygiene, and public health. Focusing on the cities of Pompeii, Herculaneum, Ostia, and Rome, Koloski-Ostrow's work challenges common perceptions of Romans' social customs, beliefs about health, tolerance for filth in their cities, and attitudes toward privacy